Educational and Exercise Intervention to Prevent Falls and Improve Participation in Subjects With Neurological Conditions: The NEUROFALL Randomized Controlled Trial - Cattaneo, Davide; Gervasoni, Elisa; Pupillo, Elisabetta; Bianchi, Elisa; Aprile, Irene; Imbimbo, Isabella; Russo, Rita; Cruciani, Arianna; Turolla, Andrea; Jonsdottir, Johanna; Agostini, Michela; Beghi, Ettore; et al. (Frontiers in Neurology, 2019)
Background: Falls, mobility impairments and lack of social support lead to participation restrictions in people with neurological conditions. The aim of this multicenter, single blinded randomized controlled trial was to test whether an educational program focusing on fall prevention and safe mobility reduces falls and increases social participation among people with neurological conditions. Methods: Ninety people with Stroke(n=25), multiple sclerosis(n=33) and Parkinson disease(n=32), median age 63(31-89), were randomized. A permuted block algorithm stratified by field center was used to allocate participants to an education group (EG, n=42) consisting of an educational program focused on fall prevention and tailored balance exercises and a control group (CG, n=48) receiving usual treatments. After baseline assessment, each participants was followed for six months with telephone contacts by blinded interviewers. Being fallers (>1 fall) and time to become a faller were used as primary outcomes. Community Integration Questionnaire (CIQ) and Instrumental Activities of Daily Living (IADL) scales assessed treatment effects on social integration and daily living activities. Results: Over a median (Interquartile Range) follow-up of 189(182-205) days, [EG =188(182-202), CG=189 (182-209)] fallers were 10 in the CG and 11 in the EG (hazard ratio 0.95, 95% confidence interval (CI) 0.45to2.5;P=0.94). At follow-up the EG scored significantly better than CG on the CIQ (+1.7 points,CI:0.1to3.3) and IADL (+2.2 points,CI:0.4to4.0). Conclusions: This educational program did not reduce the risk of falls but it improved the ability to carry out activities of daily living and decreased participation restrictions in people with neurological conditions.